Trends in Medicare Service Volume for Cataract Surgery and the Impact of the Medicare Physician Fee Schedule. (28th July 2016) - Gong, Dan; Jun, Lin; Tsai, James C.
Abstract : Objective: To calculate the associations between Medicare payment and service volume for complex and noncomplex cataract surgeries. Data Sources: The 2005–2009 CMS Part B National Summary Data Files, CMS Part B Carrier Summary Data Files, and the Medicare Physician Fee Schedule. Study Design: Conducting a retrospective, longitudinal analysis using a fixed‐effects model of Medicare Part B carriers representing all 50 states and the District of Columbia from 2005 to 2009, we calculated the Medicare payment–service volume elasticities for noncomplex (CPT 66984) and complex (CPT 66982) cataract surgeries. Data Extraction: Service volume data were extracted from the CMS Part B National Summary and Carrier Summary Data Files. Payment data were extracted from the Medicare Physician Fee Schedule. Principal Findings: From 2005 to 2009, the proportion of total cataract services billed as complex increased from 3.2 to 6.7 percent. Every 1 percent decrease in Medicare payment was associated with a nonsignificant change in noncomplex cataract service volume (elasticity = 0.15, 95 percent CI [−0.09, 0.38]) but a statistically significant increase in complex cataract service volume (elasticity = −1.12, 95 percent CI [−1.60, −0.63]). Conclusions: Reduced Medicare payment was associated with a significant increase in complex cataract service volume but not in noncomplex cataract service volume, resulting in a shift toward performing a greater proportion of complex cataract surgeries from 2005 to 2009.